Seagrasses in Batanes Province, Northern Philippines - Calumpong, Hilconida P.; Mefiez, Ernani G.; Philipps, Ronald C. (Silliman Journal, 2024)
Seagrasses were collected from 1l sites at four islands in Batanes Province, northern Philippines, during 1985 and 1986. Five species in two families and five genera are recorded for the first time.